Makna Islam dalam Al-Qur’an Perspektif Tesktualis: Studi terhadap Orientasi Tekstual dalam Penafsiran Al-Qur’an - Junaedi, Didi (AL QUDS : Jurnal Studi Alquran dan Hadis, 2023)
The Meaning of Islam in the Qur'an Textualist Perspective: A Study of Textual Orientation in Al-Qur'an InterpretationIn the treasures of exegesis, there are two orientations commonly used by mufassir in interpreting the Qur'an. First, textual orientation. Second, contextual orientation. This article aims to critically examine textual orientation in the interpretation of the Qur'an, which often only looks at the text alone, without looking at the aspects of the context surrounding the birth of the text. The focus of the study in this research is about the meaning of Islam in the Qur'an from the perspective of the textualist group. This research is library research using qualitative methods. The approach used in this research is analytical descriptive. The results of this study indicate that the textual interpretation carried out by textualist groups about the meaning of Islam emphasizes that Islam is a system of beliefs, creeds (read: religion) which are institutionalized with a set of binding doctrines. This view in turn assumes that the religion they understand is superior to others, and followers of other ways of life are considered infidels, hypocrites or wicked. Therefore, a critical review of the textual orientation in the interpretation of the Qur'an is something that is necessary.